2008
DOI: 10.1111/j.1467-646x.2008.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

UK Multinationals' Effective Use of Financial Currency‐Hedge Techniques: Estimating and Explaining Foreign Exchange Exposure Using Bilateral Exchange Rates

Abstract: Using a unique dataset of recently available accounting disclosures, this study examines the relationship between UK multinationals' stock returns and changes in the principal exchange rate to which each firm is most exposed. We find more firms with significant foreign exchange exposure estimates using this firm-specific principal currency data, compared with those exposure estimates using the broad exchange rate index data prevalent in prior studies. The cross-sectional variations in such principal-currency e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
(82 reference statements)
1
10
0
2
Order By: Relevance
“…Table IV provides the OLS regression estimation results for the equation (2) primary model, using either the firm-specific BRV-based jFXEj dependent variable (in models 1 and 3) or the broad TWI-based jFXEj dependent variable (in models 2 and 4). The BRV-based results indicate that the FHEDGE variable is significant (at a , 0.0001 level) and negative, consistent with Table III univariate results and our expectation based on extant evidence of effective financial hedging (Allayannis and Ofek, 2001;Makar and Huffman, 2008;Bartram et al, 2010).…”
Section: Explaining Fxe Estimatessupporting
confidence: 86%
See 1 more Smart Citation
“…Table IV provides the OLS regression estimation results for the equation (2) primary model, using either the firm-specific BRV-based jFXEj dependent variable (in models 1 and 3) or the broad TWI-based jFXEj dependent variable (in models 2 and 4). The BRV-based results indicate that the FHEDGE variable is significant (at a , 0.0001 level) and negative, consistent with Table III univariate results and our expectation based on extant evidence of effective financial hedging (Allayannis and Ofek, 2001;Makar and Huffman, 2008;Bartram et al, 2010).…”
Section: Explaining Fxe Estimatessupporting
confidence: 86%
“…Note: Significant at: * 10, ** 5 and *** , 0.01 percent two-sided levels Keeping in mind that such returns-based FXE estimates are net of hedging (Bartram, 2008), we posit that the smaller BRV-based jFXEj levels are due, in part, to firm-specific FX hedge techniques [11]. For example, extant research attributes the negative relation between returns-based FXE estimates and the use of FX derivatives or FX denominated debt to effective financial hedging (Allayannis and Ofek, 2001;Makar and Huffman, 2008;Bartram et al, 2010).…”
Section: Estimating Fxementioning
confidence: 99%
“…We address 1 In their Table 1, Bartram and Bodnar (2007) summarize the most important FXE studies using large samples in the non-financial sectors. Subsequent to their 2007 literature review, researchers have remained focused on the non-financial sector, given the complexity of a financial firm's FXE and risk management practices (e.g., El-Masry, Abdel-Salam, & Alatraby, 2007;Makar & Huffman, 2008). In contrast, recent studies in the financial sector that are not summarized by Bartram and Bodnar include the FXE of banks (e.g., Elyasiani, Mansur, & Pagano, 2007), and insurance and real estate (e.g., Muller & Verschoor, 2008;Li, Moshirian, Wee, & Wu, 2009).…”
Section: Building the Modelmentioning
confidence: 93%
“…Consequently, this work uses high frequency traded assets for the empirical analysis, like foreign exchange rate assets and stocks traded in the organized market. Thus, exchange rate exposure is measured as the regression coefficient of the exchange rate against the stock market (Adler & Dumas, 1983;Hodder, 1982;Makar & Huffman, 2008). Accordingly, to test the theoretical model, the empirical analysis follows the equation: Fu R − is the excess return of currency derivative.…”
Section: Empirical Researchmentioning
confidence: 99%
“…The latter implies an exchange rate effect on stock prices or firm value. In this regard, several empirical studies have found either a weak or no substantial relationship between the exchange rate and stock prices (Jorion, 1990;He & Ng, 1998;Nguyen et al, 2007;Makar & Huffman, 2008;Lee & Suh, 2012;Inci & Lee, 2014). In a multinational context, an explanation for this puzzling weak relationship is that firms have been hedging their exchange rate risk using foreign currency derivatives (Kambi & Ali, 2016;Singh, 2017;Caves, 2007;Allayannis & Ofek, 2001).…”
Section: Introductionmentioning
confidence: 99%